Early Detection of Ossification of the Posterior Longitudinal Ligament (OPLL) in Patients with Degenerative Cervical Myelopathy (DCM) - Hans Christian Uranus; Dorothea Fortuna Meita Caturwulan; Derry Arkan Prabowo; Filjordan Andrisoni Imanuel Lulupoy; Josua Kristiano Hilmanto (Universitas Pelita Harapan, 2026)
Introduction: Degenerative changes in the cervical spine leads to Degenerative Cervical Myelopathy (DCM). Ossification of posterior longitudinal ligament (OPLL) is a common cause of DCM in Asian populations and causes severe neurological deficits, which significantly impairs quality of life. Case Presentation: A 49-year-old Sunda woman presented with progressive numbness and tingling sensation followed by progressive weakness in the lower extremities. Progressive weakness then developed in the upper extremities. Physical examination revealed tetraparesis and reflexes increased in all extremities. Sensory examination revealed hypoesthesia in the right T5-T12 dermatome, and bilateral L1-S2 dermatome. She was assessed as grade 3 Nurick classification of myelopathy and has a Modified Japanese Orthopaedic Association Score (mJOA) Score of 15. Non-contrast Cervical magnetic resonance imaging (MRI) revealed continuous OPLL type at C3-C5 level. She received high dose intravenous methylprednisolone and was referred to another hospital for surgery. Discussion: OPLL has not been documented extensively in Indonesia. Early detection of DCM can be done with a mJOA score of ≤16. Conservative treatment is recommended for minimally symptomatic or high-risk surgery patients. Surgical intervention has shown significant improvement in clinical outcome, although it is not beneficial in absent or minimal myelopathy (Nurick grade 1 or 2). Conclusions: OPLL is a common cause of DCM in Asian populations. Early detection using mJOA is paramount to achieve better recovery. Conservative treatment is done for mild DCM while surgical intervention is done in moderate to severe DCM. Keywords: Conservative Treatment, Degenerative Cervical Myelopathy (DCM), Modified Japanese Orthopaedic Association Score (mJOA), Nurick Classification of Myelopathy, Ossification of Posterior Longitudinal Ligament (OPLL), Surgical Intervention